2021
DOI: 10.1186/s12906-021-03441-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and anti-inflammatory effects of Phellinus linteus mycelium

Abstract: Background The present study extensively aimed to evaluate the underlying mechanism of the immunomodulatory and anti-inflammatory effects of Phellinus linteus mycelium (PLM). Methods To assess whether PLM influences the production of markers related to inflammation, Lipopolysaccharide (LPS)-stimulated RAW264.7 cells were treated with PLM (50, 100, 200, and 500 μg/mL). Splenocyte, thymus, peritoneal exudate cells (PEC), and peripheral blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, the search for natural ingredients for immune treatment is important for the development of new therapeutics. Studies have shown that edible and medicinal mushrooms, such as Phellinus baumii and Phellinus linteus , have great therapeutic potential [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for natural ingredients for immune treatment is important for the development of new therapeutics. Studies have shown that edible and medicinal mushrooms, such as Phellinus baumii and Phellinus linteus , have great therapeutic potential [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…T and B lymphocytes play important roles in inducing effective immune responses [ 27 ]. ConA is a mitogen that stimulates only T lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 + and CD8 + T lymphocyte proportions and the CD4 + /CD8 + ratio are indicators of biological immune function [ 28 , 29 ]. During T-cell activation, IFN-γ and IL-2 are essential cytokines produced by T cells to exert immunological effects [ 27 , 30 ]. Th1 cells mostly enhance cell-mediated immunity, and Th2 cells enhance humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The immunostimulatory and antiinflammatory effects of fermented extract from the PL KCCM KSW01 strain have been reported in a nonclinical study. [9] In the present clinical trial, fermented PL extract or placebo was administered to 98 patients for 8 weeks, and the effects of PL extract on immune activity were analyzed using the LDH cytotoxicity assay.…”
Section: Introductionmentioning
confidence: 99%